Religious Moderation in Islamic Films (Buya Hamka Volume 1 Semiotic Analysis) - Siti Raudhotul Munawaroh; Rio Febriannur Rachman (CV. Murta Media Karya, 2024)
This study reveals the values ​​of religious moderation contained in the Islamic film Buya Hamka Volume 1 (hereinafter written as Buya Hamka), through Charles Sanders Pierce's semiotic analysis. The film Buya Hamka is a film that was released in 2023. This film tells the life story and thoughts of Buya Hamka, a prominent Islamic figure in Indonesia. The purpose of this study is to analyze the signs or symbols used in the film Buya Hamka to represent Islamic values ​​and religious moderation. In addition, this research aims to understand the messages that are intended to be conveyed to the audience about religious moderation. The theory used is religious moderation which was popularized by Masdar Hilmy, and also the concept of religious moderation was told by Abdul Aziz and Khoirul Anam in the book Moderasi Beragama Berlandaskan Nilai-Nilai Islam (Religious Moderation Based on Islamic Values). The method used in this study is qualitative with Charles Sanders Pierce's semiotic analysis approach. The conclusion of this study is: 1) the Buya Hamka film successfully represents religious moderation through the use of relevant signs or symbols; 2) The characters in the film show an attitude of deep understanding of religion and peaceful conflict resolution.